Depositional systems sequence stratigraphy frameworks & geological modelling of fluvial bodies - Orsini, C.; Rezaee, Reza (Geological Survey of Western Australia, 2012)
A key driver for this research is the need for a better understanding of reservoir connectivity in the Sue Group in the Whicher Range area. Litho-stratigraphic correlations tend to over-estimate the lateral connectivity of reservoir sandstones. A sequence stratigraphic framework, based on modern concepts, uses key surfaces to subdivide succession into sequences and systems tracts of genetic stratigraphic units. This approach generates a more objective prediction of intervals with optimum reservoir connectivity. The aim of this project is to develop a geological reservoir model for the southern Perth Basin focussing on the tight gas sand Permian section of Whicher Range area. There are several deeply buried, tight gas sands reservoirs in the Perth Basin that have very low permeabilities. Such a geological reservoir model will be potentially beneficial for the reservoir development and production of Whicher Range area. However, the volume and quality of data actually available to construct this geological reservoir model are limited resulting in increased uncertainty than might otherwise be the case. The application of empirical relationships, and the comparison with modern analogues, greatly assists in generating an improved and more realistic model. The presences of stratigraphic traps that involve fluvial bodies in the Whicher Range Permian section are recognized.